The Black and African American Connections to Parkinson’s Disease (BLAAC PD) study protocol - Lana M. Chahine; Naomi Louie; J Solle; Fulya Akçimen; Andrew Ameri; Samantha Augenbraun; Sabrina Avripas; Sarah Breaux; Christopher Causey; Shivika Chandra; Marissa Dean; Elizabeth A. Disbrow; et al. (BMC Neurology)
Abstract Determining the genetic contributions to Parkinson’s disease (PD) across diverse ancestries is a high priority as this work can guide therapeutic development in a global setting. The genetics of PD spans the etiological risk spectrum, from rare, highly deleterious variants linked to monogenic forms with Mendelian patterns of inheritance, to common variation involved in sporadic disease. A major limitation in PD genomics research is lack of racial and ethnic diversity. Enrollment disparities have detrimental consequences on the generalizability of results and exacerbate existing inequities in care. The Black and African American Connections to Parkinson’s Disease (BLAAC PD) study is part of the Global Parkinson’s Genetics Program, supported by the Aligning Science Across Parkinson’s initiative. The goal of the study is to investigate the genetic architecture underlying PD risk and progression in the Black and/or African American populations. This cross-sectional multicenter study in the United States has a recruitment target of up to 2,000 individuals with PD and up to 2,000 controls, all of Black and/or African American ancestry. The study design incorporates several strategies to reduce barriers to research participation. The multifaceted recruitment strategy aims to involve individuals with and without PD in various settings, emphasizing community outreach and engagement. The BLAAC PD study is an important first step toward informing understanding of the genetics of PD in a more diverse population.